2007
DOI: 10.1523/jneurosci.0126-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Proneural GeneMash1Specifies an Early Population of Telencephalic Oligodendrocytes

Abstract: The bHLH (basic helix-loop-helix) transcription factor Mash1 is best known for its role in the regulation of neurogenesis. However, Mash1 is also expressed in oligodendrocyte precursors and has recently been shown to promote the generation of oligodendrocytes in cell culture, suggesting that it may regulate oligodendrogenesis as well. Here, we show that in the developing ventral forebrain, Mash1 is expressed by a subset of oligodendrocyte precursors (OPCs) as soon as they are generated in the ventricular zone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
135
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(148 citation statements)
references
References 46 publications
12
135
1
Order By: Relevance
“…The small proportion of Olig2+/PSA-NCAM+ cells probably represents neuronal progenitors, although it is possible that a subpopulation of oligodendrocyte progenitors during very early stages of development expresses PSA-NCAM. This would be consistent with recent reports describing various oligodendrocyte progenitors subpopulations in rodents (Spassky et al, 2000;Kessaris et al, 2006, Parras et al, 2007, and possibly in humans, as we discussed previously (Jakovcevski and Zecevic, 2005b). The fact that at midgestation glia cell populations in the human brain do not express PSA-NCAM, as has been shown in rodents, might be due to either inter-species differences or difference in studied stages of development.…”
Section: Discussionsupporting
confidence: 92%
“…The small proportion of Olig2+/PSA-NCAM+ cells probably represents neuronal progenitors, although it is possible that a subpopulation of oligodendrocyte progenitors during very early stages of development expresses PSA-NCAM. This would be consistent with recent reports describing various oligodendrocyte progenitors subpopulations in rodents (Spassky et al, 2000;Kessaris et al, 2006, Parras et al, 2007, and possibly in humans, as we discussed previously (Jakovcevski and Zecevic, 2005b). The fact that at midgestation glia cell populations in the human brain do not express PSA-NCAM, as has been shown in rodents, might be due to either inter-species differences or difference in studied stages of development.…”
Section: Discussionsupporting
confidence: 92%
“…Selective expression of GFP in the neurogenic zones in the hippocampus and lateral ventricles, but not in mature neuronal cell layers in the dentate gyrus or olfactory bulb suggests that Ascl1 is transiently expressed during adult neurogenesis. In addition, the extensive, dispersed GFP expression throughout the adult brain including white matter tracts is consistent with recent reports that place Ascl1 in oligodendrocyte precursors (Battiste et al, 2007;Parras et al, 2007;Sugimori et al, 2007).…”
Section: Characterization Of Ascl1 In the Adult Brainsupporting
confidence: 90%
“…Our studies demonstrate that, at any postnatal age, at least 50% of the NG2 + cells in the SVZ are proliferative and that Cdk2 is a major molecular regulator of their proliferation throughout postnatal development (Belachew et al, 2002;Jablonska et al, 2007). The results of our previous studies also defined the following cellular and molecular properties of NG2 + cells in the SVZ Jablonska et al, 2007): i) NG2 + cells are found scattered through the wall of the lateral ventricle, but they are more abundant in the anterior SVZ; ii) NG2 + cells in the SVZ constitute approximately 12% and 3% of the total cell population at P8 and P30-60, respectively; iii) NG2 + cells in the SVZ are highly proliferative, as demonstrated by the percentages of NG2 + Ki67 + cells in the SVZ -56 and 32% at P8 and P30, respectively; iv) NG2 + cells of the SVZ express cellular markers of neural progenitor cells and stem cells, including the Lewis X antigen (LeX) (Capela and Temple, 2003), and the transcription factors Mash1, Olig2, and Dlx (Doetsch et al, 2002;Parras et al, 2004;Marshall et al, 2005;Menn et al, 2006;Kohwi et al, 2007;Parras et al, 2007); and v) NG2 + cells of the SVZ display a type-C cell phenotype, including expression of the EGFR, PSA-NCAM, and nestin (Capela and Temple, 2002;Doetsch et al, 2002). Consistent with our findings, other reports have also described the presence of NG2 + cells in the SVZ, and demonstrated diverse cellular and molecular properties of these progenitors in this neurogenic region, including co-expression of DCX Tamura et al, 2007), responsiveness to sonic hedgehog (Loulier et al, 2006), and Islet-1-induced migration into striatum (Rogelius et al, 2006).…”
Section: Discussionmentioning
confidence: 99%